2010
DOI: 10.1111/j.1440-1789.2010.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia pretreatment protects against pilocarpine-induced status epilepticus and neuronalapoptosis in immature rats

Abstract: Hypothermia has been shown to have neuroprotective effects in various models of neurological damage. However, its effects on pediatric status epilepticus (SE) are relatively unknown. In order to understand the effects of hypothermia on pediatric SE, we conducted experiments to determine the neuroprotective effects of mild hypothermic pretreatment in a model of pediatric SE. Juvenile (21-day-old) rats were subjected to mild hypothermic or normothermic conditions prior to intraperitoneal injections of pilocarpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Subsequent studies have shown that protection of the brain during early seizures has an inhibitory effect on seizures. Yu et al [31] found that hypothermia pre-treatment reduced hippocampal neuronal apoptosis in a pilocarpine-induced rat model of SE. Nitric oxide (NO) is neurotoxic [32], and it interferes with neuronal apoptosis by intervention of glycolysis and the pentose phosphate pathway in the regulation of glucose consumption [33].…”
Section: Mechanismmentioning
confidence: 98%
“…Subsequent studies have shown that protection of the brain during early seizures has an inhibitory effect on seizures. Yu et al [31] found that hypothermia pre-treatment reduced hippocampal neuronal apoptosis in a pilocarpine-induced rat model of SE. Nitric oxide (NO) is neurotoxic [32], and it interferes with neuronal apoptosis by intervention of glycolysis and the pentose phosphate pathway in the regulation of glucose consumption [33].…”
Section: Mechanismmentioning
confidence: 98%
“…Pilocarpine‐induced SE in rat pups has been used as a model of pediatric SE. Animals kept mildly hypothermic before pilocarpine injection show longer seizure latency, longer SE latency, lower spike frequency, smaller spike area, and less hippocampal apoptosis than controls (Yu et al., ). However, timing of intervention was critical in preventing neural damage and seizures in a group of near‐term fetal sheep.…”
Section: Hypothermia In Animal Models Of Epilepsymentioning
confidence: 99%
“…In rats with seizures induced by potassium channel antagonists (Yang & Rothman, ) or by fluid percussive injury (D'Ambrosio et al., ), focal cortical cooling significantly reduced seizure frequency. In rats injected with pilocarpine, hypothermia pretreatment reduced neuronal apoptosis and increased latency to SE onset (Maeda et al., ; Yu et al., ). Hypothermia also decreased brain edema and seizure frequency in rats with kainic acid–induced SE (Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%